Intentional teaching in early childhood : ignite your passion for learning and improve outcomes for young children - Sandra Heidemann; Beth Menninga; Claire Chang (Minneapolis : Free Spirit Publishing, 2019)
"Professional development resource providing advice for early childhood teachers navigating demands and changes in their careers, helping them see challenges as growth opportunities. Through self-assessment and reflection, educators reexamine their teaching philosophy, integrate new knowledge and strategies into their practice, and strengthen the impact of their teaching. Includes digital content"-- Provided by publisher
Keywords: Early childhood teachers In-service training United States; Early childhood education; Teaching Philosophy